Disordered eating, eating attitudes, and reasons for exercise among male high school cross country runners - Wadas, G.; DeBeliso, M. (The Sport Journal, 2014)
PURPOSE: This study investigated the prevalence of disordered eating behaviors among male high school cross country runners. The study identified behaviors and feelings about being an athlete, and determined relationships between motivations to exercise and disordered eating behaviors. METHODS: Sixty-eight male high school cross country runners from 12 high schools in one urban school district completed three questionnaire packets on one occasion pre-season. The EAT-26 questionnaire was used to determine prevalence of disordered eating. The ATHLETE questionnaire was used to determine psychological factors for relationships with disordered eating. The EMI-2 was used to determine motivations to exercise and the relationship to disordered eating. EAT-26 scores and data from the EMI-2 and ATHLETE questionnaires were analyzed via a Pearson Correlation Coefficient. RESULTS: A modest positive relationship existed between exercising for disordered eating behaviors versus exercising for weight management (r = 0.31: p < 0.05), the Your Body in Sports subscale (which measured drive for thinness and performance) (r = 0.36: p < 0.05), and the Feelings about Performance subscale (or Performance Perfectionism) (r = 0.26: p < 0.05). CONCLUSIONS: Risk factors associated with eating disorders exist in high school male cross country runners. Underreporting and lack of recognition of disordered eating may affect prevalence rates. Recommendations include a longitudinal study of male high school runners across the school year to determine relationships with the timing of questionnaire administration. APPLICATIONS IN SPORT: Disordered eating behaviors should be acknowledged as more than a "female only" issue. Parents, teachers, coaches, and athletic trainers may be better able to understand and help male athletes with disordered eating behaviors or an active eating disorder.